Intervention Program for Reducing Acculturative Stress of Migrant Students to India - Beri, Nimisha; Mehta, Anju (International Journal of Psychosocial Rehabilitation, 2020)
As an individual immigrates, he/she has to come into contact with a new culture that is different from his own. A new culture often challenges an individual’s values and beliefs. As they are away from family and friends and due to changes in language, academic system, etc., they are subjected to stress. “This stress, which is the result of collective stressors that occur during the process of acculturation and can result in lower mental health of the acculturating individual, is called acculturative stress” (Berry 1980). The objective of the present paper was to make an intervention program for acculturative stress. As the review of literature suggested, if this stress is not managed well, then stress will have negative effects like anxiety and depression (Thomas, 2006). The purpose of developing an intervention program is to reduce the acculturative stress and help the international students stay and adopt the new land as their future homeland. If professionals are more aware of the coping strategies, they are more likely to provide effective coping resources for international students who are experiencing problems because of adaptation difficulties. For this intervention program, it was developed having four modules, and each module comprised of different activities. Face validity was checked by taking suggestions from nine experts in the fields of education and psychology, and their suggestions were incorporated. Content validity was calculated and found to be 0.7. Thus, the intervention program found to be reliable and valid